BECOMING OF UKRAINIAN BIBLIOLOGY (galich magazines of first third of the ХХ item) - . Silevych, L. I; Melnychuk, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devoted to the complex analysis of the role of the galician universal and specialized periodicals at the beginning of XX century. in the development of Ukrainian book science. The main editions which published theoretical practical and bibliographic materials about different issues are connected with the functioning of a book in the society.